Principals' Perceptions of Technology-Based Management Transformation: A Qualitative Study in the Context of Educational Digitalization - Sugiarti, Erna; Martina, Noormalina; Dakir, Dakir; Jasiah, Jasiah (Jurnal Inovasi Pendidikan dan Sains, 2025)
In the face of educational digitalization, the transformation of management based on technology became a major challenge for school principals and teachers, with differences in perceptions, barriers, and implementation strategies. This study aimed to explore the perceptions of principals and teachers regarding the implementation of technology in school management, as well as to identify the barriers they faced and the strategies implemented during the transformation process. The study employed a qualitative approach using in-depth interviews, observations, and documentation with 10 school principals and 10 teachers from vocational schools (SMK) in Palangkaraya City. The results showed that principals had a positive perception of the technological transformation, despite facing barriers related to policies and resource limitations. On the other hand, teachers were more focused on barriers such as technological skills and the lack of training. To overcome these challenges, strategies such as technology-based training and guidance were implemented. The implications of this study highlighted the importance of policies that support ongoing technology training for both teachers and principals, as well as the development of more effective technology-based managerial systems in addressing the challenges of educational digitalization